REVIEW OF MICROFOSSIL-BEARING CLASTS WITHIN LATE MESOZOIC STRATA IN EAST ASIA: STAGED DENUDATION OF MID-MESOZOIC ACCRETIONARY COMPLEXES - Ito, Tsuyoshi; Sakai, Yusuke; Feng, Qinglai; Matsuoka, Atsushi (Ofioliti, 2017)
Late Mesozoic neritic-continental strata of East Asia show intercalations of conglomerates including microfossil-bearing clasts. Some clasts are presumed to have originated in mid-Mesozoic accretionary complexes (ACs) of East Asia. Microfossils (e.g., radiolaria, conodonts) in these clasts can provide age constraints. Relationships between rock facies and age in sequences of the mid-Mesozoic ACs have been clarified in previous studies; therefore, the rock facies and the age of the clasts offer a clue about denudation history and provenance of the mid-Mesozoic ACs. This study compiles previous studies of microfossil-bearing clasts within the Late Mesozoic in the Outer and Inner Zone of Southwest Japan and in the Gyeongsang Supergroup in the southeastern Korean Peninsula. The compilation, at present, recognizes three denudation stages (Stages A, B, and C) of the mid-Mesozoic accretionary complexes. Stage A (Oxfordian-Hauterivian) is characterized by an initial and narrow denudation. The denudation of the mid-Mesozoic ACs started at some point in this stage, but it was of limited extent. Stage B (Barremian-early Albian) is characterized by wide denudation: the mid-Mesozoic ACs became largely exposed. Afterwards, some younger geologic bodies of the mid-Mesozoic ACs, which were structurally underlying, were exposed and denuded. Stage C (late Albian–) is characterized by denudation of almost all the mid-Mesozoic accretionary complexes. This denudational evolution might be related to some tectonic and igneous events in East Asia, such as the uplift of the Tetori Group in late Hauterivian-early Barremian and the initiation of the granitic magmatic activity in middle Albian.